STUDI IMPLEMENTASI KEBIJAKAN DESENTRALISASI ADMINISTRATIF DI MUNICIPIO DILI TIMOR-LESTE - I Wayan Joniarta; I.G.A.AG Dewi Sucitawathi P; Inácio Soares; Wayan Suderana (Program Magister Ilmu Politik, Universitas Diponegoro, 2019)
This research aims to empirically elaborate the implementation of administrative decentralization in Municipio Dili Timor-Leste. This research scrutinizes human resource, financial resource, facilities and implementing structure in bureaucracy to identify implementation effectiveness. This research applies qualitative methods using interviews as methods for collecting data, observation and document reviews. This research found that the implementation of administrative decentralization has not yet been effective. There is a need for capacity building to improve government officers' capability to better off the quality of public service.